Exploring Slang Words Used by the Male and Female Main Characters in “Anyone but You” Movie - Ni Ketut Mas Ayu Mayuni; Putu Nur Ayomi (Universitas Islam Negeri Palopo, 2025)
Slang is an informal form of language commonly used in casual conversation to express identity, emotions, and social connections. It is especially prevalent in spoken English among younger generations and is frequently featured in films, music, and social media. This study analyzes the types and functions of slang used by the male and female main characters in the film Anyone but You (2023), applying Allan and Burridge’s (2006) classification. Data were collected through script analysis of approximately 120 minutes of dialogue and examined using a descriptive qualitative approach. Out of the 25 slang expressions identified, four types of slang were found: flippant, clipping, fresh and creative, and imitative. Flippant slang was the most common. Although both characters used expletive and taboo words, the male character, Ben, used slang more frequently and focused on masculine identity and peer-group language. In contrast, the female character, Bea, employed slang that was more emotionally expressive and context-dependent. Overall, the use of slang enriches the dialogue by making it more natural, relatable, and reflective of the characters’ social identities and emotions. These findings also highlight gender differences in slang usage and contribute to sociolinguistic studies on film discourse.